Prognostic signature construction of energy metabolism-related genes in pancreatic cancer - Liu, Hao; Zhang, Jianhua; Wei, Chaoguang; Liu, Zhao; Zhou, Wei; Yang, Pan; Gong, Yifu; Zhao, Yuxiang (Frontiers in Oncology, 2022)
Pancreatic cancer is the 7th leading cause of cancer death worldwide, and its incidence and mortality rate have been on the rise in recent years in Western developed countries. The specificity of the disease and the lack of appropriate treatments have resulted in a 5-year overall survival rate of only 9%. In this study, we conducted a study based on the TCGA database and GEO database and analyzed using the energy metabolism gene set to establish a prognostic model with the least absolute shrinkage and selection operator to identify 7-genes prognostic signature, and the gene expression was verified by Real-time PCR. The model was validated using a risk score calculation, and the OS rates of the 7 genes were analyzed using one-way Cox regression. The prognostic relationship between vesicle-associated membrane protein 2 (VAMP2) and pancreatic cancer patients was analyzed by OS and progression-free survival, and the prognosis was found to be significantly worse in the high-expression group. A Nomogram showed that VAMP2 was an independent prognostic factor in pancreatic cancer. Gene set enrichment analysis showed that VAMP2 upregulation was enriched in pathways associated with immune response and that VAMP2 downregulation was enriched in metabolism-related pathways. The association of VAMP2 with immune cell infiltration was analyzed for the enrichment results, and VAMP2 was found to be positively associated with all 6 immune cells. The results of this study suggest that VAMP2 is an independent prognostic factor associated with energy metabolism in pancreatic cancer and may be involved in the immune response.